Crystal structures, antibacterial, antioxidant and nucleic acid interactions of mononuclear, and tetranuclear palladium(II) complexes containing Schiff base ligands. Issue 18 (16th September 2016) - Moosun, S. B.; Bhowon, M. G.; Hosten, E. C.; Jhaumeer-Laulloo, S.
Abstract: Two new palladium complexes, [Pd(dpbs )Cl] (1 ) and [Pd4 (dbbs )4 ] (2 ) (where (dpbs )2  =  o, o ′-( N, N′ -dipicolinyldene)diazadiphenyl disulfide and (dbbs )2  =  N, N′ -(1, 1′-dithio-bis(phenylene))-bis(salicylideneimine)), have been synthesized and characterized by analytical and spectral (electronic, IR, 1 H, 13 C spectroscopy) techniques. The structures of1 and2 have been solved by single-crystal X-ray diffraction experiments, which indicate distorted square planar coordination geometries around palladium(II) by O, N, and S donors. The metal chelates have been screened for their antibacterial and antioxidant activities, and compared with their respective ligands. The binding properties of the complexes have been studied by electronic absorption, emission spectroscopy, and viscosity measurements. The competitive fluorescence study with ethidium bromide and the effect of iodide concentration on ﬂuorescence of the complex-DNA system have been investigated. All these experimental results suggest that palladium complexes strongly bind to DNA, presumably via groove binding. The thermodynamic parameters, enthalpy change (ΔH°), and entropy change (ΔS°) were calculated by the Van't Hoff equation, suggesting hydrogen bonds play a predominant role in the binding of complexes to DNA. Abstract :